ANALISIS MANAJEMEN KOMUNIKASI INTERNAL (Studi Deskriptif Kualitatif pada Yakes Telkom) - Ida Rapida Djachrab (Masoem University, 2019)
This research was conducted with the aim to understand and explore the management of internal communication conducted by the Telkom Health Foundation (Yakes Telkom) in the city of Bandung. This research is a qualitative research where data collection is obtained through interviews, observation, and documentation. The technique of selecting informants uses purposive techniques. The data analysis technique used is the interaction model of Miles and Huberman. The study was located at the Takes Telkom Head Office, Jl Cisanggarung no. 2 Bandung.The results of the management analysis of internal communication at Yakes Telkom are (1) The process of management and management of the system in Foundation is done by planning, organizing, moving, directing, coordinating, and supervising. The process is to achieve the goal, namely to minimize miss communication and strengthen the communication relationship between one employee and another; (2) Development of internal communication systems in foundations concerning lack of human resources due to age; (3) Improving the quality of internal communication within the foundation by means of the Foundation to foster social relations with joint picnics and community service; (4) The implementation of business communication for the foundation's internal public is seen from verbal and non-verbal communication, communication patterns that are applied in two directions, selection of channels and communication media verbally and in writing, as well as the completion of the coffee morning and interpersonal humanist and psychological approaches to effective strategies when a problem occurs.